Sleep interventions designed to improve athletic performance and recovery: A systematic review of current approaches - Bonnar, D.; Bartel, K.; Kakoschke, N.; Lang, C. (Sports Medicine, 2018)
Athletes experience various situations and conditions that can interfere with their sleep, which is crucial for optimal psychological and physiological recovery as well as subsequent performance. Conventional sleep screening and intervention approaches may not be efficacious for athletes given their lifestyle, the demands of training and travel associated with interstate/international competition. Objectives: The present systematic review aimed to summarize and evaluate sleep intervention studies targeting subsequent performance and recovery in competitive athletes. Based on the findings, a secondary aim was to outline a possible sleep intervention for athletes, including recommendations for content, mode of delivery and evaluation. Methods: A systematic review was conducted based on the PRISMA guidelines in May 2016 with an update completed in September 2017. Ten studies met our inclusion criteria comprising a total of 218 participants in the age range of 18-24 years with athletes from various sports (e.g., swimming, soccer, basketball, tennis). A modified version of the quality assessment scale developed by Abernethy and Bleakley was used to evaluate the quality of the studies. Results: The included studies implemented several sleep interventions, including sleep extension and napping, sleep hygiene, and post-exercise recovery strategies. Evidence suggests that sleep extension had the most beneficial effects on subsequent performance. Consistent with previous research, these results suggest that sleep plays an important role in some, but not all, aspects of athletes` performance and recovery. Conclusion: Future researchers should aim to conduct sleep interventions among different athlete populations, compare results, and further establish guidelines and intervention tools for athletes to address their specific sleep demands and disturbances.